2014
DOI: 10.1371/journal.pone.0084877
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Microbes Sustain Youthful Serum Testosterone Levels and Testicular Size in Aging Mice

Abstract: The decline of circulating testosterone levels in aging men is associated with adverse health effects. During studies of probiotic bacteria and obesity, we discovered that male mice routinely consuming purified lactic acid bacteria originally isolated from human milk had larger testicles and increased serum testosterone levels compared to their age-matched controls. Further investigation using microscopy-assisted histomorphometry of testicular tissue showed that mice consuming Lactobacillus reuteri in their dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
115
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(122 citation statements)
references
References 57 publications
5
115
2
Order By: Relevance
“…An earlier study reported that the absence of gut microbiota influenced testosterone levels [41] in accordance with our observation of a lower intratesticular level of testosterone in GF mice compared to SPF and CBUT mice. A recent study demonstrated that dietary supplementation of the probiotics Lactobacillus reuteri increased and restored testosterone levels in aging mice [42]. We could not detect any differences in the expression levels of genes specific for Leydig cell or the levels of mRNA encoding enzymes involved in testosterone production (e.g., Insl3, Hsd3b1, Hsd17b11, cyp11a1 and cyp19a ).…”
Section: Discussioncontrasting
confidence: 73%
“…An earlier study reported that the absence of gut microbiota influenced testosterone levels [41] in accordance with our observation of a lower intratesticular level of testosterone in GF mice compared to SPF and CBUT mice. A recent study demonstrated that dietary supplementation of the probiotics Lactobacillus reuteri increased and restored testosterone levels in aging mice [42]. We could not detect any differences in the expression levels of genes specific for Leydig cell or the levels of mRNA encoding enzymes involved in testosterone production (e.g., Insl3, Hsd3b1, Hsd17b11, cyp11a1 and cyp19a ).…”
Section: Discussioncontrasting
confidence: 73%
“…The consumption of Lactobacillus paracasei probiotic bacteria, and their preferred food source (FOS, fibre) present within the Flortec supplement, is known to enhance intestinal barrier function, thereby reducing levels of endotoxin exposure and inflammation. We believe that this is a likely mechanism behind the improvement in testicular function seen in these men, especially as earlier reports have shown that Lactobacillus probiotic primarily mediates its beneficial effect on testicular function via modulation of the immune system (Poutahidis et al, 2014).…”
mentioning
confidence: 66%
“…Interestingly, the microbiome generally (63) and the probiotic Lactobacillus reuteri specifically have been shown to increase testosterone in mice, effects that could be mimicked by interfering with IL-17A signaling, a proinflammatory cytokine (64). Immunoregulatory microbes act on regulatory dendritic cells, which in turn bias T-cell differentiation toward Treg and away from IL-17-producing T helper 17 (Th17) cells (65,66).…”
Section: Discussionmentioning
confidence: 99%